Plant regeneration and Agrobacterium-mediated transformation in Indian mustard (Brassica juncea) - Disha Kamboj; Ram C.Yadav; Amit Singh; Neelam R.Yadav; Dhiraj Singh (Journal of Oilseed Brassica, 2026)
Using seedling explants, a highly efficient and reproducible plant regeneration and transformation systemwas developed in Brassica juncea genotypes RH-406 and RH-555. Hypocotyl and cotyledon explantsexcised from in vitro-grown 5-days-old seedlings were cultured on MS medium supplemented with differentconcentrations and combinations of growth regulators. Cotyledon explants grown on MS mediumsupplemented with 1 and 2.5 mg/L BAP produced higher per cent shoot formation in genotypes RH-555(60.3±4.19) and RH-406 (64.9± 1.42), respectively. Among the eight rooting media used for root formation inregenerated shoots, maximum rooting response was obtained on MS medium supplemented with 0.2 mg/LNAA. Among the regenerated plants, 81.8 % in RH-406 and 67% in RH-555 survived when transferred onsand and soil in 1:1 mixture in pots. Transformation protocol was developed in genotype RH-406 using GUSreporter gene and hypocotyls and cotyledon explants. Histochemical GUS assay showed that cotyledon andhypocotyl explants respectively, had 75% and 80% transient GUS expressions.